Pengukuran Penerimaan Sistem Informasi EWSKIA Berdasarkan Persepsi Pengguna dengan Menggunakan Technology Acceptance Model - Widodo, Aris Puji; Agushybana, Farid; Jati, Sutopo Patria (Universitas Diponegoro, 2018)
This study is a quantitative research that has a goal to measure the level of user acceptance of EWSKIA information system based on perception. EWSKIA is a healthcare application tool used to perform the process of recording and monitoring the health conditions of pregnant and childbirth mothers. The model used in this research is using Technology Acceptance Model (TAM) model with 3 variables, namely Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and Behavioral Intention to Use (BITU). This variable consists of independent variables namely PEOU and PU, and the dependent variable is BITU. The respondents were 145 midwives from Grobogan District, Temanggung Regency and Salatiga City. Data analysis to conduct causal relationships between variables using Partial Least Square (PLS). The results of this study statistically show that the 3 hypotheses of H1, H2, and H3 adopted from the TAM model have a positive and significant influence. This is indicated by the value of the regression coefficient is positive and the coefficient of P value is less than 0.005